2018
DOI: 10.1002/car.2507
|View full text |Cite
|
Sign up to set email alerts
|

Children in Identified Sexual Images – Who Are they? Self‐ and Non‐Self‐Taken Images in the International Child Sexual Exploitation Image Database 2006–2015

Abstract: Child sexual abuse and exploitation material has drawn concern and legislative attention since the turn of the century, and the work to identify children in the images has been a prioritised task through international cooperation. The International Child Sexual Exploitation Image Database (ICSE DB) includes more than 8000 identified victims from nearly 50 countries. The database contains considerable important information about child abuse image crimes. The general aim of this study was to quantify the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Two-thirds of all the images were classified as coercive. Almost two-thirds of the children identified were white females; 44.3% of the images were self-taken and of these most were taken in a coercive relationship (Quayle, Jonsson, Cooper, Traynor, & Svedin 2018, cited in ECPAT 2018). Another study of 3,503 18-year-old Swedish youth indicated that for 6.5% of those who reported sexual abuse, the abuse had been documented in pictures or videos; these children also experienced more severe forms of CSA, such as penetrative sex, recurrent sexual abuse and multiple offenders (Svedin, 2012cited in ECPAT 2018 In a dataset of 1,965 cases (from the UK ICSE, NCMEC database of identified children), 61% of cases involved single victims, while images of multiple victims were more likely to involve pubescent children.…”
Section: Description Of Observed Cemmentioning
confidence: 99%
“…Two-thirds of all the images were classified as coercive. Almost two-thirds of the children identified were white females; 44.3% of the images were self-taken and of these most were taken in a coercive relationship (Quayle, Jonsson, Cooper, Traynor, & Svedin 2018, cited in ECPAT 2018). Another study of 3,503 18-year-old Swedish youth indicated that for 6.5% of those who reported sexual abuse, the abuse had been documented in pictures or videos; these children also experienced more severe forms of CSA, such as penetrative sex, recurrent sexual abuse and multiple offenders (Svedin, 2012cited in ECPAT 2018 In a dataset of 1,965 cases (from the UK ICSE, NCMEC database of identified children), 61% of cases involved single victims, while images of multiple victims were more likely to involve pubescent children.…”
Section: Description Of Observed Cemmentioning
confidence: 99%
“…Manipulating or coercing a child to produce a nude or sexual image emerges in this study as a common and harmful strategy among online child sex offenders, casting debates on so‐called ‘sexting’ in a new light. The authors note that: ‘Much of the debate about sexting activity has placed responsibility for the images being misused squarely on the child’ (Quayle et al ., , p. 235).…”
Section: The Paradox Of Self‐manufactured Imagesmentioning
confidence: 97%
“…The paper by Ethel Quayle and colleagues () provides a content analysis of images from the International Child Sexual Exploitation Image Database from 2006 – 2015, which spans the period over which self‐production of images by minors became more frequent. Their analysis distinguishes between self‐taken images and those taken by others, finding that self‐produced images have increased in frequency over time.…”
Section: The Paradox Of Self‐manufactured Imagesmentioning
confidence: 99%
“…Moreover, a relationship was observed between engaging in selfdisclosure on social media and becoming a victim of blackmail on social media, with those disclosing more information being at a greater risk of becoming a victim of blackmail (Kopecký 2016). Similarly, those who were willing to share intimate personal photographs were also at risk of becoming a victim of blackmail on social media (Hamilton-Giachritsis, Hanson, Whittle and Beech 2017; Kopecký 2017; Quayle, Jonsson, Cooper, Traynor and Svedin 2018;Van Ouytsel et al 2017).…”
Section: Vulnerability To Victimisationmentioning
confidence: 99%